Cleansing oil formulations using avocado oil (Persea americana) with identification and antioxidant test on oil - Hana Anisa Fatimi; Dava Aurel Divani (Pharmaciana, 2026)
Taking care of your facial skin to achieve fresh, clean, radiant, supple, soft, and healthy-looking skin is the dream of many people. Dirty facial skin, caused by the use of makeup, exposure to sunlight, dust, and vehicle fumes, can lead to sebum buildup, which in turn can cause acne and severe inflammation. Therefore, this study developed a cleansing oil formulation for more beneficial skin care using natural avocado oil (Persea americana) with various concentrations of cocamidopropyl betaine. These formulations were formulated and tested through a series of tests, including organoleptic tests, homogeneity tests, viscosity tests, pH tests, and cleaning power tests. Antioxidant activity tests using the DPPH method and identification tests using TLC on avocado oil. The optimal result of this study is the F1 formulation using a 5% concentration of cocamidopropyl, which has a stable preparation, is good at removing dirt and makeup, and is effective in protecting the skin from damage caused by free radicals because it contains highly active antioxidants with an IC50 of 4.486 mg/L, since avocado oil has an IC50 value below 50 ppm. From the study's results, it can be concluded that the lower the cocamidopropyl betaine content, the higher the viscosity, pH, and cleaning power of the cleansing oil.